Tanggapan Guru TK dan PAUD Terhadap Sosialisasi dan Penilaian dalam Lomba Stratifikasi Sekolah Sehat Tahun 2025 di Kota Surakarta - Ana Riolina; Ikhwan Tri Julian; Qothrunnada Fathin Fadhilah (Publikasi Indonesia, 2026)
The School Health Program is a strategic national initiative aimed at improving students’ health from early childhood. Its success relies heavily on the understanding and involvement of kindergarten and early childhood education teachers as key implementers. This study examines teachers’ responses to the socialization and assessment stages of the 2025 School Health Program in Surakarta City. A descriptive quantitative method with a post-test-only design was employed, involving 92 respondents from kindergarten and PAUD institutions. A validated Likert-scale questionnaire was used to measure responses related to the socialization process and assessment activities. The findings reveal that 63.04% of respondents rated the socialization process as excellent, while 77.17% rated the assessment process as excellent. Teachers perceived the socialization as clear, interactive, and effectively delivered by competent facilitators. During the assessment stage, teachers noted professionalism, objectivity, and adequate opportunities for schools to present their actual conditions. Overall, the program received strong acceptance and demonstrated significant potential in improving school health standards. The study recommends enhancing the distribution of information and strengthening transparency in assessment procedures to further optimize program implementation.